2022
DOI: 10.3390/pharmacy10040076
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Comprehensive Healthcare Providers’ Opinions, Preferences, and Attitudes towards Deprescribing (CHOPPED Questionnaire)

Abstract: Successful implementation of deprescribing requires exploring healthcare professionals’ opinions, preferences, and attitudes towards deprescribing. The aim of this study was to develop and validate the questionnaire exploring healthcare providers’ opinions preferences and attitudes towards deprescribing (CHOPPED questionnaire). This was a cross-sectional on-line survey. A comprehensive 58-item questionnaire, in two versions (for pharmacists and physicians), was developed through an extensive literature review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…It is important to state that deprescribing is very new concept in the investigated setting and this may have led to healthcare providers being more familiar with the concept being the ones willing to participate in the study, creating a bias. Nevertheless, a significant advantage of this research is a strong methodology for the development and validation of the tool used in this research with confirmed face, content, construct, and criterion validity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to state that deprescribing is very new concept in the investigated setting and this may have led to healthcare providers being more familiar with the concept being the ones willing to participate in the study, creating a bias. Nevertheless, a significant advantage of this research is a strong methodology for the development and validation of the tool used in this research with confirmed face, content, construct, and criterion validity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey consisted of three parts: sociodemographic questions, a comprehensive healthcare provider’s opinions, preferences, and attitudes towards deprescribing questionnaire (CHOPPED), and a case vignette (analysis not included herein). The development and validation of the CHOPPED questionnaire have been described elsewhere [ 18 ]. Two versions of the questionnaire are available, one for pharmacists (with 38 items) and one for physicians (with 36 items).…”
Section: Methodsmentioning
confidence: 99%
“…Details on the study design were described in a previous publication 25 . Primary care physicians and pharmacists were sent an invitation (with two remainder invitations 4 and 8 weeks after the initial invite) and the link to the survey containing the case vignette via email.…”
Section: Methodsmentioning
confidence: 99%
“…Stop medication a 159 (12%) Opioid (32), moxonidine (25), furosemide (25), NSAID (19), bisoprolol (15), allopurinol (10), lactulose (7), zolpidem (5), PPI (5), alprazolam (4), escitalopram (4), amlodipine/valsartan (4), ASA (3), tamsulozin…”
Section: Deprescribingmentioning
confidence: 99%